Comparison of high temperature and high Reynolds number water flows between PTB and NMIJ. (December 2016) - Furuichi, Noriyuki; Cordova, Leopoldo; Lederer, Thomas; Terao, Yoshiya
Abstract: Bi-comparison for high temperature and high Reynolds number water flows was performed between Physikalische-Technische Bundesanstalt (PTB) and National Metrology Institute of Japan (NMIJ) using differential pressure meters. The flowrate range considered herein was from 250 m 3 /h to 740 m 3 /h and the temperature range was from 20 °C to 80 °C. The Reynolds number based on the pipe diameter ranges from 4.4×10 5 to 3.6×10 6 . The expanded uncertainty of volumetric flowrate with a coverage factor k =2 is 0.040% for PTB and 0.070% for NMIJ. The differential pressure meters as the transfer meter were a throat-tapped flow nozzle and an orifice. The results for both flow meters were in good agreement between the two labs. The difference in the average discharge coefficient at the same Reynolds number ranged from −0.05% to 0.03% for the flow nozzle and from −0.01% to 0.05% for the orifice. The results of the comparison indicate a high level of consistency between PTB and NMIJ for high temperature and high Reynolds number water flows. Highlights: The bi-comparison for high temperature water flow was carried out between PTB and NMIJ. The transfer meters are orifice and flow nozzle. The deviation between PTB and NMIJ is within 0.05%. The results of the comparison indicate a high level of consistency for high temperature and high Reynolds number water flows.